IMPORTANCE AND PERFORMANCE ANALYSIS OF DISTANCE EDUCATION FOR RADIO AND TELEVISION UNIVERSITY OF CHINA STUDENTS IN CHINA - Wang, Xinyan; Intravisit, Apichart (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This study aims to measure students’ perception on importance and performance of Radio and Television University of China (RTUC), with intention to help improve the university’s business. Student satisfaction is one of the important indexes of university ranking, and it is also an important reference index when students choose university. As a radio and television university, its students are mainly adults who have entered the social work, students in order to be more competitive in the workplace to promote the continuing education of academic qualifications. Unlike full-time students who are influenced by a variety of factors, adult students will focus on student satisfaction when choosing a school, so improving college satisfaction is important for RTUC enrollment, and studying the impact criteria of different variables on student satisfaction can help RTUC improve student satisfaction and thus better help universities attract students to enroll. Variables effecting RTUC’s students’ satisfaction in the distance education industry of china includes eight attributes: they are, RTUC’s general service, registration guide, tutorial, practice, learning material, examination, media, and, cost/value for money. Survey conducted on RTUC’s 401 students via questionnaire of 44 questions finds no significant difference between their perceptions on importance and performance of all variables. This is a research use quantitative method and use important and performance analysis to evaluate the result.